XAS/WAXS time-resolved phase speciation of chlorine LDH thermal transformation: Emerging roles of isovalent metal substitution - Carvalho, Hudson W.P. [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Leroux, Fabrice; Meneau, Florian; Briois, Valérie (American Chemical Society (ACS), 2013)
The XAS/WAXS time-resolved method was applied for unraveling the complex mechanisms arising from the evolution of several metastable intermediates during the degradation of chlorine layered double hydroxide (LDH) upon heating to 450 °C, i.e., Zn2Al(OH)6·nH2O, ZnCuAl(OH)6·nH2O, Zn2Al 0.75Fe0.25(OH)6·nH2O, and ZnCuAl0.5Fe0.5(OH)6·nH2O. After a contraction of the interlamellar distance, attributed to the loss of intracrystalline water molecules, this distance experiences an expansion (T > 175-225 °C) before the breakdown of the lamellar framework around 275-295 °C. Amorphous prenucleus clusters with crystallo-chemical local order of zinc-based oxide and zinc-based spinel phases, and if any of copper-based oxide, are formed at T > 175-225 °C well before the loss of stacking of LDH layers. This distance expansion has been ascribed to the migration of Zn II from octahedral layers to tetrahedral sites in the interlayer space, nucleating the nano-ZnO or nano-ZnM2O4 (M = Al or Fe) amorphous prenuclei. The transformation of these nano-ZnO clusters toward ZnO crystallites proceeds through an agglomeration process occurring before the complete loss of layer stacking for Zn2Al(OH)6· nH2O and Zn2Al0.75Fe0.25(OH) 6·nH2O. For ZnCuAl(OH)6·nH 2O and ZnCuAl0.5Fe0.5(OH)6· nH2O, a cooperative effect between the formation of nano-CuO and nano-ZnAl2O4 amorphous clusters facilitates the topochemical transformation of LDH to spinel due to the contribution of octahedral CuII vacancy to ZnII diffusion. © 2013 American Chemical Society.
Keywords: layered double hydroxide; quick-EXAFS; thermal decomposition; WAXS; Co-operative effects; Interlamellar distance; Layered double hydroxides; Metastable intermediate; Thermal transformations; Time-resolved methods; Aluminum; Chlorine; Chlorine compounds; Decomposition; Iron compounds; Pyrolysis; Zinc oxide; Zinc